It wasn’t me! Motor activation from irrelevant spatial information in the absence of a response - Bundt, Carsten; Bardi, Lara; Abrahamse, Elger L.; Brass, Marcel; Notebaert, Wim (Frontiers in Human Neuroscience, 2015)
Embodied cognition postulates that perceptual and motor processes serve higher-order cognitive faculties like language. A major challenge for embodied cognition concerns the grounding of abstract concepts. Here we zoom in on abstract spatial concepts and ask the question to what extent the sensorimotor system is involved in processing these. Most of the empirical support in favor of an embodied perspective on (abstract) spatial information has derived from so-called compatibility effects in which a task-irrelevant feature either facilitates (for compatible trials) or hinders (in incompatible trials) responding to the task-relevant feature. This type of effect has been interpreted in terms of (task-irrelevant) feature-induced response activation. The problem with such approach is that incompatible features generate an array of task-relevant and –irrelevant activations (e.g., in primary motor cortex), and lateral hemispheric interactions render it difficult to assign credit to the task-irrelevant feature per se in driving these activations. Here we aim to obtain a cleaner indication of response activation on the basis of abstract spatial information. We employed transcranial magnetic stimulation (TMS) to probe response activation of effectors in response to semantic, task-irrelevant stimuli (i.e. the words left and right) that did not require an overt response. Results revealed larger motor evoked potentials (MEPs) for the right (left) index finger when the word right (left) was presented. Our findings provide support for the grounding of abstract spatial concepts in the sensorimotor system.